Curcumin Formulations and Trials: What’s New in Neurological Diseases - Stella Gagliardi; Carlo Morasso; Polychronis Stivaktakis; Cecilia Pandini; Veronica Tinelli; Aristides Tsatsakis; Davide Prosperi; Miriam Hickey; Fabio Corsi; Cristina Cereda (Molecules, 2020)
Curcumin’s pharmacological properties and its possible benefits for neurological diseases and dementia have been much debated. In vitro experiments show that curcumin modulates several key physiological pathways of importance for neurology. However, in vivo studies have not always matched expectations. Thus, improved formulations of curcumin are emerging as powerful tools in overcoming the bioavailability and stability limitations of curcumin. New studies in animal models and recent double-blinded, placebo-controlled clinical trials using some of these new formulations are finally beginning to show that curcumin could be used for the treatment of cognitive decline. Ultimately, this work could ease the burden caused by a group of diseases that are becoming a global emergency because of the unprecedented growth in the number of people aged 65 and over worldwide. In this review, we discuss curcumin’s main mechanisms of action and also data from in vivo experiments on the effects of curcumin on cognitive decline.